Energy Dispersive X-Ray Fluorescence Spectroscopy and Applications in Material Science - Tsompopoulou, E.; Mergia, K. (HNPS Advances in Nuclear Physics, 2019)
Energy dispersive X-ray fluorescence spectroscopy (EDXRF) is a powerful non-destructive technique used to determine the elemental composition of materials. The current work focuses on the installation and optimization of the operation of the EDXRF system developed by Amptek Inc. Furthermore, XRF elemental analysis results of alloys candidate for fusion reactor applications are presented